2021
DOI: 10.1182/blood-2021-147522
|View full text |Cite
|
Sign up to set email alerts
|

Development of an MDM2 Degrader for Treatment of Acute Leukemias

Abstract: Introduction Acute myeloid leukemias (AMLs) are characterized by suppressed cell death pathways which promote leukemic blast survival. TP53 acts as a tumor suppressor gene in AML and is found mutated or deleted in 10-15% of patients. In a majority of cases though, TP53 is wild-type. Other mechanisms including MDM2 over-expression lead to reduced TP53 activity. MDM2 acts as a negative regulator by direct binding of TP53 and mediating TP53 degradation through ubiquitination. MDM2 itself is a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…9 ). The three co-opted E3 ligases, VHL , XIAP , and AHR , have been explored against cancer targets in PROTAC 12 , 22 , 44 46 , and their expression patterns in tumor and normal tissues suggest extensive future usage, such as XIAP in breast cancer (Fig. 4c , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9 ). The three co-opted E3 ligases, VHL , XIAP , and AHR , have been explored against cancer targets in PROTAC 12 , 22 , 44 46 , and their expression patterns in tumor and normal tissues suggest extensive future usage, such as XIAP in breast cancer (Fig. 4c , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two other PROTAC–MDM2 degrader molecules have been reported, but their structures have not been disclosed. Marcellino et al reported the development of the PROTAC–MDM2 degrader XY-27 using an undisclosed MDM2 inhibitor tethered to a ligand of the VHL E3 ubiquitin ligase [ 86 ]. VHL was selected due to its higher expression in acute myelogenous leukemia (AML) compared to other cancers, and its use can potentially improve the potency and specificity in AML.…”
Section: Targeting the Protein–protein Interaction Between Mdm2 And P53mentioning
confidence: 99%